A preliminary checklist of Melastomataceae in Fraser’s Hill, Selangor - Mohd Zaki, Nur Syahindah; Che Amri, Che Nurul Aini; Zohari, Ahmad fitri; Abdul Rahman, Mohamad Ruzi; Mohd Yunus, Noor Syaheera; Shamsuri, Nur Shahrul I’zzati; Go, Rusea; Shahari, Rozilawati (Jabatan Perhutanan Semenanjung Malaysia, 2023)
A study on the diversity of Melastomataceae in Selangor State Park, Fraser Hill, Selangor was conducted from 26 August to 30 August 2019. This study was carried out to identify and record the diversity of Melastomataceae species. The materials obtained for this study were collected from sampling sites and prepared as herbarium vouchers. Morphological data such as plant habit, stem, leaves and flower variation were recorded. Based on this study, 17 species of Melastomataceae have been collected and examined. Ten genera namely Clidemia, Diplectria, Dissochaeta, Medinilla, Melastoma, Oxyspora, Phyllagathis, Pternandra, Sonerila, and Tibouchina were recorded. Four endemic species were recorded, viz. Phyllagathis hispida, Sonerila albiflora, S. integrifolia and S. rudis. It mostly can be found in the open area with full sunlight. An updated checklist of Melastomataceae has been prepared for future references and comparison.